Value Based Education to Develop Attitude of Inclusive - Adiba, Lu'lu'a Farah; Zahruddin, Zahruddin; Bahrissalim, Bahrissalim (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2023)
Education is ultimately a humanizing experience. There-fore it can’t be separated from social activities. The school as a facilitator has to be safe and proper for all of the students' needs. The educator has the responsibility to make the students learn by creating the supporting environment. One of the important values in social activities is about being inclusive. Students with different interests or backgrounds usually had few friends. This case is extremely important because it will affect student’s habits in the future. They might feel inferior in the communities. In this case value based education has an important role. It was needed for the foundation as the establishment of a student inclusivism attitude. By the values acknowledged, students can understand more about acceptance and tolerance for any diversity that might happen at school. This research aims to describe the value based education to develop the inclusivism attitude. This study used a library research approach with content analysis technique to display the data. As a result, value based education can be used as a preventive action for misbehaving exclusivism. The values that had been taught help students to develop an inclusive and open attitude toward a variety of multicultural thoughts including the different interests.